Fungal Communities in Soils: Soil Organic Matter Degradation - Větrovský, Tomáš; Štursová, Martina; Baldrian, Petr (Methods in molecular biology, 2016)
Stable isotope probing (SIP) provides the opportunity to label decomposer microorganisms that build their biomass on a specific substrate. In combination with high-throughput sequencing, SIP allows for the identification of fungal community members involved in a particular decomposition process. Further information can be gained through gene-targeted metagenomics and metatranscriptomics, opening the possibility to describe the pool of genes catalyzing specific decomposition reactions in situ and to identify the diversity of genes that are expressed. When combined with gene descriptions of fungal isolates from the same environment, specific biochemical reactions involved in decomposition can be linked to individual fungal taxa. Here we describe the use of these methods to explore the cellulolytic fungal community in forest litter and soil.
Keywords: fylogeneze; Soil Microbiology; izotopové značení; metagenomika; Cellulose; DNA, Fungal; půdní mikrobiologie; Metagenomics; Substrate Specificity; regulace genové exprese u hub; Isotope Labeling; substrátová specifita; houby; DNA fungální; Phylogeny; Fungi; Gene Expression Regulation, Fungal; celulosa